Gall stone ileus with cholecystoduodenal fistula - Elangkumaran Vellode Manoharan; P Kanakarajan; G Ramkumar; E Selvakumar (Apollo Medicine)
Gallstone ileus and cholecystoduodenal fistula are rare and life-threatening conditions which are due to cholelithiasis and recurrent attacks of cholecystitis. It predominantly affects female population. The signs and symptoms are non-specific, sometimes only established during surgery. Prompt surgical management would avoid the complications and reduce the hospital stay.